SPIRITUALITAS ECKHART “SUNDER WARUMBE PADA TOKOH HENDRA” MENCINTAI TANPA MENGAPA? DALAM NOVEL “MY IDIOT BROTHER” KARYA AGNES DAVONAR - Doys Ivone (IAKN Ambon, 2020)
Everyone has a different spiritual experience, including how to love someone or something. People who love others mostly have a background in the interests of giving each other. Therefore, there are those who easily understand the meaning of love and fight for and share love easily, but there are also those who experience the opposite. This paper focuses on one of the works of Agnes Davonar in the novel